2021
DOI: 10.3389/fpsyg.2021.596543
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Predictors of COVID-19 Prevention Behavior in Hungarian Women Across Different Generations

Abstract: BackgroundAge related differences were found in prevention behavior, showing that older individuals tend to be the most proactive. The aim of the study was the identification of psychological predictors on COVID-19 prevention behavior in women, across four generations. In addition, the predictive role of the psychological variables was explored through the lens of negative and positive information processing perspective on total and domain-specific COVID-19 prevention behavior.MethodsA cross-sectional research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 74 publications
2
8
1
Order By: Relevance
“…Consistent with previous studies [49][50][51], our findings indicate that women are more likely than men to adopt preventive behaviors against COVID-19. Generally, women, compared with men, may have greater motivation to promote health [52], perceive the risk of a disease more deeply, and look into disease information more frequently [18].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous studies [49][50][51], our findings indicate that women are more likely than men to adopt preventive behaviors against COVID-19. Generally, women, compared with men, may have greater motivation to promote health [52], perceive the risk of a disease more deeply, and look into disease information more frequently [18].…”
Section: Discussionsupporting
confidence: 92%
“… 23 For example, prevention behavior in the context of COVID-19 was predicted by a tendency to focus on negative information in many generations. 24 Similarly, in the matter of vaccine uptake, negative information seems to elevate the chance of refusal or avoidance of the vaccines. 19 , 25 Vaccine hesitancy is associated with negative information processing and this can explain the overestimation of negative effects of vaccination and the underestimation of beneficial ones.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, in the United States researchers found that individuals with greater psychological flexibility experienced reduced psychological distress during the COVID-19 pandemic [10]. Other studies have further investigated psychological flexibility as it relates to the pandemic in different outcomes, as well as the potentially protective effects of psychological flexibility on mental health during the pandemic [26][27][28][29]. As such, it is clear that psychological flexibility is an important modifiable transdiagnostic predictor of well-being and behavioral compliance during global adversity.…”
Section: Discussionmentioning
confidence: 99%